2015
DOI: 10.2298/mpns1512382m
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes of health care science students toward older people

Abstract: There is increasing evidence on the correlation between education, knowledge and attitudes toward older people which suggests that by acquiring better insights into all aspects of ageing through their education the students develop more positive attitudes and interest in working with older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 7 publications
(15 reference statements)
2
10
2
5
Order By: Relevance
“…This indicates that students with higher knowledge about ageing, may possess more positive attitudes towards older adults or vice versa. This finding is consistent with results from previous studies 8,13,22,23 . A positive impact on students' attitude has been shown with improved training in geriatric care and exposure to older adults 24 .…”
Section: Discussionsupporting
confidence: 94%
“…This indicates that students with higher knowledge about ageing, may possess more positive attitudes towards older adults or vice versa. This finding is consistent with results from previous studies 8,13,22,23 . A positive impact on students' attitude has been shown with improved training in geriatric care and exposure to older adults 24 .…”
Section: Discussionsupporting
confidence: 94%
“…The level of knowledge about old age allows predicting the intensity of positive and negative attitudes towards older people and is the strongest predictor of those attitudes. The intensity of positive attitudes is also predicted by the subjective assessment of the quality of contact with older people [ 36 , 46 , 47 , 48 , 49 , 50 ]. In view of those results, Zawada [ 51 ] has stressed that gerontological education should be included in education programs from kindergarten to university.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the finding is highly probably due to Hawthorne effect. Education is a mechanism of proven efficacy for acquiring new approaches and positive attitudes of health professionals toward the elderly (Rodgers & Gilmour 2011, Milutinovic et al 2015. Coffey & Whitehead performed a systematic review on the subject and showed that most published research found an association between education and knowledge towards ageing, which can in turn impact improvement of attitudes toward aging and spark interest in working with the elderly (Coffey & Whitehead 2015).…”
Section: Discussionmentioning
confidence: 99%